2010
DOI: 10.1107/s0108768110003423
|View full text |Cite
|
Sign up to set email alerts
|

Predicted crystal structures of tetramethylsilane and tetramethylgermane and an experimental low-temperature structure of tetramethylsilane

Abstract: No crystal structure at ambient pressure is known for tetramethylsilane, Si(CH(3))(4), which is used as a standard in NMR spectroscopy. Possible crystal structures were predicted by global lattice-energy minimizations using force-field methods. The lowest-energy structure corresponds to the high-pressure room-temperature phase (Pa3, Z = 8). Low-temperature crystallization at 100 K resulted in a single crystal, and its crystal structure has been determined. The structure corresponds to the predicted structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…6(a). The obtained space group of Pa-3 is consistent with the theoretical calculation, 14 in which the Pa-3 phase was predicted by global lattice-energy minimizations using force-field methods. At 1.0 GPa, the TMGe has the lattice parameter of a = 10.5968(4) Å, which is similar to that of TMS.…”
Section: B Determination Of High-pressure Phasessupporting
confidence: 84%
See 1 more Smart Citation
“…6(a). The obtained space group of Pa-3 is consistent with the theoretical calculation, 14 in which the Pa-3 phase was predicted by global lattice-energy minimizations using force-field methods. At 1.0 GPa, the TMGe has the lattice parameter of a = 10.5968(4) Å, which is similar to that of TMS.…”
Section: B Determination Of High-pressure Phasessupporting
confidence: 84%
“…The CH 3 groups are expected to play an important role in understanding the interesting physical and chemical properties of the tetra-alkyl compounds of group IVa elements. [13][14][15][16][17][18][19] At low temperature, the CH 3 groups become non-equivalent and exhibit intermolecular interactions. 18,19 In addition, the CH 3 groups show various interesting behaviors at high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…For substances with "normal" melting curve, cooling down and compression in a small P-T region often produce equivalent solid phases. 14 Low-temperature TMS would undergo α → β → γ phase transitions and only γ phase is stable when heated to 118 K, which should be consistent with lowtemperature crystallization to transform into a single crystal in the temperature range of 80 and 159 K. 12 Solid phase II of TMS observed at 9.2-16.2 GPa, therefore, has a possibly similar structure as the γ phase, that is, with the same point group symmetry, although the detailed space group might be different. Additionally, a study on possible crystal structures of TMS was performed by global lattice-energy minimization using force-field methods.…”
Section: Resultsmentioning
confidence: 82%
“…Additionally, a study on possible crystal structures of TMS was performed by global lattice-energy minimization using force-field methods. 12 The results indicated that the Pnma space group is the second low-energy structure for TMS and the same with γ phase. As seen in Table I, solid phase II has some changes only from CH 3 stretch and CH 3 rocking in view of molecular structure, but phase III has a dramatic change on C-Si skeletal deformation related to intramolecular interaction besides of CH 3 vibrational modes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation